2019
DOI: 10.1002/jper.18-0756
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators for marginal bone resorption around implants in function for at least 4 years: A retrospective longitudinal study

Abstract: Background Marginal bone stability is considered one of the most important issues in implant dentistry. It is essential to understand how various factors influence bone resorption around implants. The purpose of this retrospective longitudinal study was to identify potential risk indicators associated with marginal bone resorption around implants in function for at least 4 years. Methods Several systemic‐related, intraoral‐related, implant‐related factors were collected. Marginal bone level change (MBLC) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
3
12
1
Order By: Relevance
“…Upon further analysis of the present data synthesis, MBL differed significantly between the two groups, favoring implants with wider KT. This finding corroborates the results of former observation, which over a 4‐year period detected significantly more MBL at implants with KT < 2 mm compared to the control sites (Mameno et al 2020). Consequently, as the previous meta‐analysis based on four prospective clinical studies indicates, soft‐tissue augmentation for KT gain significantly improved gingival and plaque indices and yielded more stable MBLs, relative to non‐augmented sites, thereby confirming that adequate KT at an implant site is associated with superior peri‐implant soft‐ and hard‐tissue health and stability (Thoma et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Upon further analysis of the present data synthesis, MBL differed significantly between the two groups, favoring implants with wider KT. This finding corroborates the results of former observation, which over a 4‐year period detected significantly more MBL at implants with KT < 2 mm compared to the control sites (Mameno et al 2020). Consequently, as the previous meta‐analysis based on four prospective clinical studies indicates, soft‐tissue augmentation for KT gain significantly improved gingival and plaque indices and yielded more stable MBLs, relative to non‐augmented sites, thereby confirming that adequate KT at an implant site is associated with superior peri‐implant soft‐ and hard‐tissue health and stability (Thoma et al.…”
Section: Discussionsupporting
confidence: 93%
“…This finding corroborates the results of former observation, which over a 4-year period detected significantly more MBL at implants with KT < 2 mm compared to the control sites (Mameno et al 2020).…”
Section: Bone Stabilitysupporting
confidence: 93%
“…Recent research also identified these factors as important. 9,44,45 The most frequently used diagnostic criteria by both groups included radiographic bone loss, clinical probing and presence of bleeding and suppuration. Both groups evaluated implant exposure and mucosal recession as a Answers ranged from "1" = "disagree strongly" to "5" = "agree strongly".…”
Section: Discussionmentioning
confidence: 99%
“…3 In a recent retrospective longitudinal study, poor plaque control was reported to be the main risk factor for peri-implant bone loss. 10 Given the infectious etiology of peri-implantitis, the majority of efforts aimed…”
Section: ⅲ Discussionmentioning
confidence: 99%